The Impact of Fluroxypyr Drift on Soybean Phytotoxicity and the Safety Drift Thresholds - Qingqing Zhou; Songchao Zhang; Tianqi Lin; Yuxuan Jiao; Chen Cai; Chenchen Xue; Jinwen Ye; Xinyu Xue (Agriculture)
Maize–soybean intercropping can increase soybean yields and stabilize maize yields, and this practice has been widely promoted in China. Fluroxypyr is a recommended herbicide for maize seedlings, and its drift will cause phytotoxicity to neighboring soybean seedlings. A laboratory toxicity test was performed on soybeans by using a mobile bioassay spray tower. It showed that both the carrier volume and the drift deposition rate of fluroxypyr significantly influenced soybean fresh weight. The soybean fresh weight inhibition rate increased with the increase in the drift deposition rate, especially in the range of 1% to 6%, and soybean fresh weight decreased rapidly. The lack of fit R2 was 0.6875, with a 9% maximum deviation between experimental values and simulated values. The drift deposition rate upper threshold for mild phytotoxicity (10% fresh weight inhibition rate, ED10) was determined to be 3.35%, while the threshold for no phytotoxicity (0% fresh weight inhibition rate, ED0) was 1.01%. To ensure soybean safety, isolation devices and anti-drift nozzles were installed on the boom sprayer to maintain drift below ED0 or, at most, ED10. Maize seedling strip weed control field tests showed that the highest drift deposition rate was 0.689% under the carrier volume of 330 L·ha−1. There was no phytotoxicity observed on soybeans after 21 days of application, which was consistent with laboratory research results. In this study, the phytotoxicity risk and safe thresholds for the fluroxypyr drift on soybean seedlings were established, which provide a theoretical basis for the safe production of soybeans.